On making the immeasurable measurable : a search for spirituality in painting practice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Harvey, Amber (Massey University, 2009)
No abstract available
Keywords: Spirituality in art; Painting; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies::410202 Fine arts studies (incl. sculpture and painting)